Класифікація цвітіння деревних і кущових листопадних рослин помірного клімату - Gorb, V.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2008)
Unified classification of flowering in temperate deci duous species of therophyllous trees and shrubs are presented. It is based on the principle of the normal morphogenesis of generative buds. All flowering types are subdivided into two types: the main one and the secondary one. The last one contains six sub types: retarded, preceded, reversal, repairing, re montant, and prolific. Retarded and reparing sub types are subdivided into two groups each: meteo- and climatogenic, meteo- and mechanogenic, respectively. Preceded subtype is subdivided into eight groups: endo- , meteo- , phytopatho- , entomo- , chemo- , thermo- , mechano- , and climatogenic.